2019
DOI: 10.2967/jnumed.119.236059
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of68Ga-PSMA PET/CT for Detection of Phosphatase and Tensin Homolog Expression in Prostate Cancer: A Pilot Study

Abstract: Our purpose was to explore the value of 68 Ga-prostate-specific membrane antigen (PSMA) PET/CT for detection of phosphatase and tensin homolog (PTEN)-loss prostate cancer. Methods: We retrospectively enrolled 75 patients who underwent multiparametric MRI and 68 Ga-PSMA PET/CT before radical prostatectomy. Lesions were outlined on pathologic images, and regions of interest were drawn on matched multiparametric MRI and PET/CT images. Imaging parameters, including average apparent diffusion coefficient and SUV ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…High PSMA expression is associated with defective DNA damage repair and PTEN loss, whereas patients with low 68 Ga-PSMA expression have poor survival (29)(30)(31). Since bone biopsies in this study were not obtained from metastases with low 68 Ga-PSMA uptake, these sites are underrepresented in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…High PSMA expression is associated with defective DNA damage repair and PTEN loss, whereas patients with low 68 Ga-PSMA expression have poor survival (29)(30)(31). Since bone biopsies in this study were not obtained from metastases with low 68 Ga-PSMA uptake, these sites are underrepresented in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a relatively new nuclear imaging modality 68 Ga-PSMA PET/CT imaging with good PCa diagnosis and staging performance has become increasingly utilized to evaluate PCa aggressiveness, especially in patients with biochemical recurrence after surgery (Sachpekidis et al, 2016;Koerber et al, 2017;Wang et al, 2020). PSMA can be coupled with different chelators and labeled with corresponding radionuclides for different purposes.…”
Section: Introductionmentioning
confidence: 99%
“…However, a limited number of studies have focused on the primary prostatic lesion [14,15]. We previously showed that 68 Ga-PSMA PET/CT had higher sensitivity for the detection of lymphadenopathy and visceral metastasis compared with mpMRI, and described the clinical characteristics of intra-prostatic primary lesions including tumour size, shape, and location [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%